Global problem of the impact of air pollution on human health: the importance and role of pharmacists - Vujanović, Dragana (Archives of Pharmacy, 2022)
From smog hanging over cities to smoke inside the home, air pollution poses a major threat to health across the globe. Almost all of the global population (99%) is exposed to air pollution levels that put them at increased risk for diseases. Health consequences of short-term and long-term exposure to polluted air (outdoor or indoor) are different and clearly defined. Air pollution was the 4th leading risk factor for early death worldwide in 2021, surpassed only by high blood pressure, tobacco use, and poor diet. The Burden of Disease from air pollution, or Global Burden of Disease (GBD) is an approach to global descriptive epidemiology. GBD estimates of disease and death due to pollution are based on pollution risk factor-disease pairs for which there is currently broad scientific consensus for a causal relation between exposure and adverse health outcome(s), and for which reliable assessments of global risk can be made. WHO monitors the exposure levels and health impacts (i.e. deaths, DALYs) of air pollution at the national, regional and global level from ambient (outdoor) and household air pollution. Air quality has improved in many high-income countries over the past several decades, while dangerous levels of air pollution persist in low- and middle-income countries. It is imperative that health systems work in synergy to mitigate the impact of air pollution on people’s health and quality of life. Community pharmacists are taking on an evolving role in the management of respiratory illness by providing comprehensive education and patient-centered care.